Integrated microRNA-mRNA analysis provides new insights into gonad coloration in the sea urchin Strongylocentrotus intermedius - Wu, Boqiong; Jiao, Renhe; Cui, Dongyao; Zhao, Tanjun; Song, Jian; Zhan, Yaoyao; Chang, Yaqing (Frontiers in Marine Science, 2023)
Comparative microRNA (miRNA) and mRNA transcriptome analyses were performed on Strongylocentrotus intermedius of the same sex with significant gonadal color differences. The results indicated that 1) the color of female gonads was generally superior to that of males. 2) Comparative and integrated miRNA and mRNA transcriptome analyses identified differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs) in female and male individuals with significant gonadal color differences. Common and sex-specific DEGs and “DEM-DEG” pairs involved in carotenoid absorption, accumulation, and transformation were identified as candidates correlated with gonad coloration in S. intermedius. Collectively, the results from this study have enriched our knowledge of the process of sea urchin gonad coloration and should provide additional clues for increasing the gonad quality of commercial sea urchins from molecular and metabolic aspects.